1994
DOI: 10.1901/jaba.1994.27-197
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Functional Analysis of Self‐injury

Abstract: This study describes the use of an operant methodology to assess functional relationships between self-injury and specific environmental events. The self-injurious behaviors of nine developmentally disabled subjects were observed during periods of brief, repeated exposure to a series of analogue conditions. Each condition differed along one or more of the following dimensions: (1) play materials (present vs absent), (2) experimenter demands (high vs low), and (3) social attention (absent vs noncontingent vs co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
2,051
1
28

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,345 publications
(2,135 citation statements)
references
References 38 publications
12
2,051
1
28
Order By: Relevance
“…Results showed that all parents provided escape (via removal of demands), access to attention, and access to tangibles, to some extent following IMB, with escape and attention being the most common parental response. Piazza, Fisher, et al then conducted functional analyses by comparing test conditions (escape, attention, and tangible) to a control condition, using methods similar to those described by Iwata, Dorsey, Slifer, Bauman, andRichman (1982/1994). Results showed that the functional analyses were effective in identifying the function(s) of IMB, with escape and attention being the most commonly identified reinforcers and escape being the single most commonly identified reinforcer.…”
mentioning
confidence: 99%
“…Results showed that all parents provided escape (via removal of demands), access to attention, and access to tangibles, to some extent following IMB, with escape and attention being the most common parental response. Piazza, Fisher, et al then conducted functional analyses by comparing test conditions (escape, attention, and tangible) to a control condition, using methods similar to those described by Iwata, Dorsey, Slifer, Bauman, andRichman (1982/1994). Results showed that the functional analyses were effective in identifying the function(s) of IMB, with escape and attention being the most commonly identified reinforcers and escape being the single most commonly identified reinforcer.…”
mentioning
confidence: 99%
“…Response options are based on sources of reinforcement that are commonly identified in experimental/analog assessments (e.g., Iwata et al , 1994. This means that the opportunity for mentalistic and otherwise irrelevant information is removed (i.e., information that is derived from a dualistic worldview).…”
Section: Closed-ended Indirect Assessmentsmentioning
confidence: 99%
“…The vast majority of functional-assessment articles published in the Journal of Applied Behavior Analysis, focus on functional analysis and, more often than not, functional analysis procedures similar to those described by Iwata, Dorsey, Slifer, Bauman, & Richman (1982/1994. This robust literature on functional analysis includes a number of procedural variations, all involving manipulation of antecedents and/or consequences, that effectively identify behavioral function in a majority of cases (up to 93% if multiple modifications are made to the procedure; Hagopian, Rooker, Jessel, & DeLeon, 2013).…”
Section: The Process Of Functional Assessmentmentioning
confidence: 99%
“…The research on functional assessment rating scales is actually quite mixed, with some studies suggesting poor reliability (these studies primarily compared results of an indirect assessment to results of the traditional functional analysis documented by Iwata et al, 1982Iwata et al, /1994, but others documenting adequate reliability and validity (e.g., Carter & Horner, 2009;Doggett, Edwards, Moore, Tingstrom, & Wilczynski, 2001;Healy, Brett, & Leader, 2013;McIntosh et al, 2008;Watkins & Rapp, 2013). Studies suggesting adequate agreement typically compared results of indirect assessment to experimental functional analysis more broadly.…”
Section: A Hierarchical Approach To Functional Assessmentmentioning
confidence: 99%
See 1 more Smart Citation